Research progress in preparation and effect of surface coating on SiC fibers - KANG Weifeng; XING Xin; ZHANG Yu; YAN Dexuan; GOU Yanzi (Cailiao gongcheng, 2023)
SiC fiber is one of the common reinforcements for ceramic matrix composite (CMC) due to its superior characteristics such as low density, high tensile strength, excellent high temperature resistance and oxidation resistance. The preparation of coating on the surface of SiC fiber can not only improve the mechanical properties, high temperature resistance, oxidation resistance and electromagnetic functional properties of the fiber itself, but also effectively improve the bonding properties of the interface between the fiber and the matrix to promote the fracture toughness and mechanical properties of the composite. The preparation methods of surface coatings on SiC fiber were firstly reviewed in this paper by elaborating on the basic processes and related research progress of etching, deposition, chemical vapor infiltration, and precursor derived methods, and the advantages and disadvantages of different preparation methods were compared. Then the effects of coatings on SiC fibers and their reinforced composite materials were reviewed. Finally, the development trend of surface coating on SiC fibers was briefly summarized. The combination of experimental research and computational simulation can be used to simulate the real service environment of SiC fibers coatings, and the performance of fibers under extreme service conditions can be improved by preparing thermal barrier composite coatings.